Dual-emission ratiometric fluorometric platform using Cu@NCDs/eosin system for sensitive detection of metformin: Pharmacokinetic studies in normal and disease states - Jardan, Yousef A. Bin; El-Wekil, Mohamed M.; Mostafa, Aya M.; Barker, James; Ali, Almontaser Bellah H. (Microchemical journal, 2025)
[Display omitted] •New ratiometric fluorometric detection of metformin using Cu@NCDs/eosin dual-emission system.•Unique sensing mechanism based on simultaneous fluorescence quenching and enhancement.•Successful monitoring of metformin in healthy and renally impaired subjects.•Dual-response mechanism offers improved accuracy over conventional methods.•Demonstrated potential for therapeutic drug monitoring applications. A novel ratiometric fluorometric method has been developed for the determination of metformin (MET) using a dual-emission system composed of copper ion-modified nitrogen-doped carbon dots (Cu2+/NCDs) and eosin. The sensing mechanism exploits MET’s inherent properties, specifically its strong positive charge and high complexation affinity due to amino groups, which enable simultaneous quenching of eosin fluorescence and restoration of NCDs fluorescence through Cu2+ion complexation. The method demonstrates excellent selectivity owing to its ratiometric sensing mechanism, along with notable linearity and sensitivity in MET detection. Comprehensive characterization of the as-prepared carbon dots was conducted using various spectroscopic and microscopic techniques, accompanied by detailed mechanistic studies to elucidate the underlying detection principles. The practical applicability of the method was validated through successful determination of MET in rat plasma samples. Furthermore, the method enabled effective monitoring of MET levels in both healthy rats and those with experimentally induced renal dysfunction, providing valuable insights into the drug’s pharmacokinetic parameters under different physiological conditions. These findings establish this ratiometric fluorometric approach as a promising analytical tool for MET determination in complex biological matrices.